Case Report: 3D printing of customized combined guides assisting total hip arthroplasty for treatment of fused hip: a case report - Wang, Xingyu; Jiang, Yifeng; Wang, Zhe; Zeng, Yu; Chen, Jiaxin; Li, Hongbo; Liao, Guanxiang; Dong, Xieping (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundConverting a fused hip to total hip arthroplasty (THA) presents considerable surgical challenges. Traditional surgical techniques frequently result in malalignment of osteotomy planes and inaccurate prosthetic placement, leading to a high incidence of perioperative complications.Case summaryThis report describes a 64-year-old male patient who underwent debridement surgery for right tuberculous hip arthritis 52 years ago. Following the operation, the joint gradually fused spontaneously, causing limited mobility. Over the past 4 years, the patient has experienced right knee pain and an unstable gait. The pathological fusion of the hip joint posed great challenges for THA, particularly in determining the osteotomy plane, ensuring adequate bone support, and reconstructing the acetabular rotation center. Using CT data, we designed and 3D printed a customized acetabular prosthesis with a series of combined guide systems, which allowed precise osteotomy and prosthetic implantation during the surgery. However, the patient developed a Mycobacterium avium infection following the procedure. As a result, debridement surgery, replacement of the acetabular liner, and combined pharmacological treatment were completed. Ultimately, the infection was controlled. A 5.5-year follow-up exhibited an improvement in the Harris hip score from 41 preoperatively to 90 postoperatively. The patient’s ability to perform activities of daily living improved significantly, and radiological follow-up indicated good prosthetic positioning without signs of loosening or displacement.ConclusionThe use of 3D-printed customized combined guides in THA offers a precise and safe treatment option for patients with hip joint fusion, effectively overcoming surgical challenges associated with altered anatomy. Moreover, this approach provides a reliable treatment reference for similar complex cases. The occurrence of M. avium infection in this patient underscores the importance of perioperative infection control and prompt management in patients with a history of tuberculosis.